1988
DOI: 10.1104/pp.88.4.1136
|View full text |Cite
|
Sign up to set email alerts
|

Plant Hormone Interaction and Phenolic Metabolism in the Regulation of Russet Spotting in Iceberg Lettuce

Abstract: Russet spotting (RS2) is a physiological disorder that may develop during postharvest transport and storage of iceberg (crisphead) lettuce (Lactuca sativa L.). This disorder is characterized by the appearance along both sides of the midrib of numerous small brown spots that may spread over the leaf blade in severe cases (9). .Exposure to ppm levels of ethylene at storage temperatures around 5°C induces RS development (14). Susceptibility to RS depends on storage temperature, ethylene concentration, oxygen and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(91 citation statements)
references
References 9 publications
4
84
0
3
Order By: Relevance
“…Several studies have described a relationship between the PAL activity in lettuce leaves and browning. [6][7][8] We also showed that inhibitors of the shikimate and phenylpropanoid pathways repressed the browning of cut lettuce and that regulating polyphenol biosynthesis was essential to repress the browning.…”
Section: )mentioning
confidence: 81%
See 1 more Smart Citation
“…Several studies have described a relationship between the PAL activity in lettuce leaves and browning. [6][7][8] We also showed that inhibitors of the shikimate and phenylpropanoid pathways repressed the browning of cut lettuce and that regulating polyphenol biosynthesis was essential to repress the browning.…”
Section: )mentioning
confidence: 81%
“…It is well known that PAL is induced by stress such as ethylene or wounding. [6][7][8][9] Cutting lettuce for minimal processing induces a stress in lettuce. On the other hand, the PAL activity of the cut lettuce treated by heat shock was only a little detected during storage.…”
Section: Fig 3 Effects Of Heat Shock Treatment On the Pal Activity mentioning
confidence: 99%
“…The head and leaves are rich in several minerals, vitamins and important source of dietary antioxidants (Ke and Saltveit, 1988;Nicolle et al, 2004). With the increasing awareness on ill effect of chemical faming on human health and environment, the demand of organic lettuce for salad and other preparation is increasing sharply both in domestic and international market.…”
Section: Introductionmentioning
confidence: 99%
“…However, we suppose that phenylalanine ammonia lyase (PAL; EC 4.3.1.24), one of the key enzymes of polyphenol biosynthesis, is induced during cold storage and that the synthesized polyphenols are oxidized by PPO to form a brown pigment. In cut lettuce, the PAL activity is induced by cutting or injury, which leads to the accumulation of phenolic compounds and enzymatic browning during cold storage (Lopez-Galvez et al, 1996;Ke and Saltveit, 1988;Hisaminato et al, 2001). Induction of PAL activity can be repressed by heat-shock treatment to inhibit browning of lettuce (Loaiza-Velarde et al, 1997;Saltveit, 2000;Murata et al, 2004).…”
Section: Introductionmentioning
confidence: 99%